Assessment of platelet function in patients with Raynaud's syndrome. Issue 2 (February 1984) - Hutton, R A; Mikhailidis, D P; Bernstein, R M; Jeremy, J Y; Hughes, G R; Dandona, P
Abstract : Platelet function was studied in 11 patients with Raynaud's syndrome and 11 healthy controls. Platelets obtained from patients with Raynaud's syndrome were significantly more responsive to adrenaline, produced more thromboxane A2, and were resistant to prostaglandin inhibitors (prostacyclin and prostaglandin E1) of platelet aggregation. Platelets from control subjects and patients with Raynaud's syndrome were more resistant to prostaglandin inhibitors when reactions were carried out at 27 degrees C rather than at 37 degrees C. Patients with Raynaud's syndrome also had significantly increased plasma concentrations of beta-thromboglobulin, fibrinogen, and circulating platelet aggregates. In an attempt to elicit local platelet responses, the forearms of control subjects and patients with Raynaud's syndrome were cooled in water tanks and platelet function tests performed before and after cooling. No significant difference in the results was observed. The potential role of platelets in the pathogenesis of Raynaud's syndrome is discussed.